Risk assessment of bilge water discharges in two Baltic shipping lanes. (January 2018) - Magnusson, Kerstin; Jalkanen, Jukka-Pekka; Johansson, Lasse; Smailys, Vytautas; Telemo, Paul; Winnes, Hulda
Abstract: Environmental concentrations and effects of bilge water contaminants in two Baltic Sea areas were estimated from modelling of discharge rates and analytical data on bilge water from seven ships. Biodegradation of bilge water oil was accounted for and annual water concentrations were estimated to peak in late spring, which coincides with the beginning of a period with extensive biological activities in the sea. Concentrations on bilge water metals were calculated both as water concentrations and as the annual contribution of metals to sediments. The predicted bilge water concentrations of oil and metal in the marine environment were estimated to be 4 to 8 orders of magnitude lower than reported toxic concentrations. However, available toxicity data are based on short term exposure and there is to date limited information on toxic effects of the small but chronically elevated contaminant concentrations derived from bilge water discharge and other operational shipping activities. Highlights: Estimations were made of seawater concentrations of oil and metals from discharge of bilge water in Baltic Sea shipping lanes. Calculations used modelled data on discharge, measured bilge water concentrations and literature data on oil degradation. Discharges lead to chronically elevated levels of pollutants but 4 to 8 orders of magnitude below known toxic concentrations.